Sol-gel synthesis of Zn doped HA powders and their conversion to porous bodies - Naqshbandi, Abreeq; Sopyan, Iis; -, Gunawan; -, Suryanto (Trans Tech Publications Ltd., Switzerland, 2014)
Abstract. The present study was aimed at fabricating porous ceramic scaffolds via polymeric sponge method for biomedical applications using as synthesized Zinc doped Hydroxyapatite (ZnHA) powders. Zn doped HA powders were prepared via sol-gel method using diammonia hydrogen phosphate [(NH4)2HPO4] and calcium nitrate tetrahydrate [Ca(NO3)2.4H2O] as starting materials. The obtained powders were then used for the preparation of porous ZnHA scaffolds via polymeric sponge method. The green porous bodies so developed by impregnating cellulosic sponges with HA slurries, were subjected to sintering process at a temperature of 1300 °C. Field- emission scanning electron microscopy (FESEM) was used to observe the surface morphology of the powder and sintered porous sample. The structure and crystallinity of (Zn)HA powder and the sintered porous samples was analyzed using X-ray diffractometer whereas Fourier transform infrared spectroscopy (FTIR) was used to determine the presence of various phases in the powder. FESEM results showed the formation of agglomerates at an increased Zn concentration. The morphology of the porous samples showed high degree of fusion and densification with an increase in Zn concentration. Preliminary mechanical testing results show that maximum compression strength of HA porous bodies was 0.12 MPa.